Sosialisasi Makna Komunikasi Slogan T.O.S.S (Temukan, Obati, Sayangi Bayi Stunting) dalam Mengatasi Naiknya Angka Stunting - Nurhadi, Zikri Fachrul; Febrina, R. Ismira; Erfan, Muhamad (Penerbit Goodwood, 2024)
Purpose: The aim of this research is to explain the use of the T.O.S.S slogan from the aspects of motif, experience and meaning, especially for the community in Giriawas Village, Cikajang Garut. Methodology: The method used in this service activity is an interactive lecture accompanied by group discussion. This activity adopts a structured approach through planning, observation, implementation and evaluation stages, which is designed to achieve the main objective, namely increasing public understanding of stunting prevention through socializing the meaning of the slogan T.O.S.S. Results: The results of this service show that there is an increase in understanding and knowledge for the participants after carrying out this activity, this is done through pre-test and post-test. Conclusions: In this service, the motif that was awakened in the community of Giriawas Village, Cikajang Garut, the TOSS communication slogan became a motivation that was easy to remember, able to unite specific convergence steps. The experience and approach to this program succeeded in building a good perception. The communication meaning of the TOSS slogan for society contains different meanings depending on how someone interprets the TOSS slogan in implementing it. Limitations: The limitations of this service have not been socialized more widely, only involving a few components in Giriawas Village. Contribution: This service makes a significant contribution to understanding the meaning of the TOSS slogan, so that it can increase understanding and knowledge of the meaning of this slogan.